REVIEW ON NASA ROGA (NASAL DISEASES) IN AYURVEDA MEDICINE WITH SPECIAL REFERENCE TO THE PINASA (CATARRH) IN SRI LANKAN TRADITIONAL MEDICINE - Nanayakkara Vidanagamage Yasangi Diloopa; E.D. Thanuja Priyangani Gunarathna (International Journal of Ayurveda and Pharma Research, 2021)
Pinasa (Catarrh) is an inflammatory disease of respiratory mucosa accompanied by sneezing, cough, headache, rhinorrhea, itching in throat and eyes. This cascade challenges the management of the disease and ultimately leads to negative impact to quality of life of the patient. At present, intervention strategies have been implemented in the management based on the herbal formulae with the light of Sri Lankan traditional medicine (SLTM). The study is focused to compile this scattered indigenous knowledge on Pinasa and compare them with the findings of Ayurveda medicine to explore the diagnosis and management gaps in both Ayurveda and SLTM. Data collection was done through documentary surveys, interviews and observations. The study revealed that the Pinasa has been considered as collective phenomena of Pratishyaya, Dushta Pratishyaya and Apinasa in Ayurveda medicine. Similarities has been found in etiology, clinical features and treatments stratergies in SLTM and Ayurveda medicine but types of the disease are varying. Pinasa was classified into 12 and 19 sub types in SLTM while 05 sub types of Pratishyaya have been described in Ayurveda medicine. Snehana (oleation), Swedana (fomentation) and Nasya (inhalation) were mentioned as external treatment modalities in Ayurveda medicine while same regimn are mentioned in SLTM but in different medical terminologies. Decoctions, pills, Kalka, Choorna and porridge were administered as internal remedies in both the medical system with different formulae while Nidana Parivarjana and Patyapatya Sewana considered as preventive measures. It can be concluded that the knowledge on Pinasa in SLTM is crucial important to conduct further research studies to find effective management along with novel preparation for Pinasa.